Self Disclosure Perempuan di Media Sosial WhatsApp (Studi Pada Siswi SMAN 4 Kendari) - rahmadani .; Muslan .; Asmurti . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research is motivated by the rapid development of communication technology, particularly the social media platform WhatsApp, which has altered the patterns of interaction and self-disclosure among female adolescents at SMAN 4 Kendari. The phenomenon of excessive disclosure of personal information on social media poses serious risks such as online harassment, cyberbullying, and identity theft. This study aims to describe the stages of self-disclosure among females on WhatsApp and to analyze the impacts or consequences of privacy disturbances experienced by the female students of SMAN 4 Kendari. Using a descriptive qualitative method, data were collected through observation, in-depth interviews, and documentation, then analyzed using Social Penetration Theory and Communication Privacy Management (CPM) Theory. The results indicate that self-disclosure is carried out gradually through the WhatsApp Status feature, ranging from the orientation stage to the stable exchange stage, where students often use mediators such as quotes or songs to protect their emotional privacy. Although WhatsApp serves as a space for positive self-image validation and strengthening social bonds, such openness also triggers privacy turbulence in the form of bullying and data misuse. In conclusion, the students' level of self-disclosure is at a moderately deep level, and the existence of negative impacts encourages them to evaluate their behavior by tightening their privacy boundaries (boundary thickening).